2017
DOI: 10.1038/srep40844
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Auxin Response Factor 19 affects seed size in the woody perennial Jatropha curcas

Abstract: Seed size is a major determinant of seed yield but few is known about the genetics controlling of seed size in plants. Phytohormones cytokinin and brassinosteroid were known to be involved in the regulation of herbaceous plant seed development. Here we identified a homolog of Auxin Response Factor 19 (JcARF19) from a woody plant Jatropha curcas and genetically demonstrated its functions in controlling seed size and seed yield. Through Virus Induced Gene Silencing (VIGS), we found that JcARF19 was a positive up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 71 publications
(98 reference statements)
0
32
0
Order By: Relevance
“…An ARF18 mutation was found to increase seed weight and silique length in rapeseed, possibly by affecting cell wall development (Liu et al ., ). In Jatropha curcas , auxin treatment increases seed size, possibly by up‐regulating expression of an ARF19 homolog (Sun et al ., ). Our results suggested that ARF6/8 may also regulate seed size in camelina.…”
Section: Discussionmentioning
confidence: 97%
“…An ARF18 mutation was found to increase seed weight and silique length in rapeseed, possibly by affecting cell wall development (Liu et al ., ). In Jatropha curcas , auxin treatment increases seed size, possibly by up‐regulating expression of an ARF19 homolog (Sun et al ., ). Our results suggested that ARF6/8 may also regulate seed size in camelina.…”
Section: Discussionmentioning
confidence: 97%
“…In maize, an auxin biosynthesis mutation, de‐18 , reduced auxin content and seed size (Bernardi et al ., ), whereas in Medicago truncatula , a mutation that alters auxin distribution within reproductive tissues led to small seeds (Noguero et al ., ). In rice, the gene Big Grain 1 is thought to increase seed size by affecting auxin transport (Liu et al ., ), whereas in Jatropha curcas , overexpression of the Auxin Response Factor 19 gene resulted in larger seeds (Sun et al ., ). These results are consistent with our findings.…”
Section: Discussionmentioning
confidence: 97%
“…The probable reasons for the above results may be related to physiological requirements, the structural limitations of seeds, and the microenvironment surrounding the seeds. Recent studies have shown that the environment experienced by plants during seed formation had important effects on seed characteristics [13], such as temperature [28], stand density, age of the mother tree [12], and hormone levels of the mother tree [29]. Therefore, seed size needs to be integrated with the external environmental factors of seed formation in explaining the natural regeneration of forests.…”
Section: Discussionmentioning
confidence: 99%